Ecology as paradigm for social sciences - Ferlito, Sergio (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2021)
'Ecology’ is a polysemic word. Nevertheless, there is a remarkable difference between the word itself, such as it is used in common speech, and the concept which the term refers to. While usually the word is variously related to the environment, the underlying concept is univocal and has a wider and deeper core than the word: it points out a connective (or comprehensive) way of think and implies a worldview; so, the concept suggests an epistemic idea. This sharp distinction appears clearly when one compares ‘shallow’ ecology with ‘deep’ ecology. Deep ecology contains a powerful methodological suggestion that should be adopted by social sciences, including law, ethics and politics.